Ahimsa as a Way of Life: Relevance of Jain Ethics in the Modern World - Mondal, Kuntal (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The philosophical and ethical significance of Ahimsa, a fundamental tenet of Jainism, is examined in this essay, along with its applicability to contemporary moral dilemmas. In my view, Jain ethics provides a thorough moral framework that goes beyond simply abstaining from violence and encourages a wholistic lifestyle based on self-control, compassion, and respect for all living things. The study starts by examining the philosophical underpinnings of Jain ethics, emphasizing the close relationship between the Ahimsa doctrine and the metaphysical conception of the soul, karma, and the interconnectedness of all living things. It delves more into how Ahimsa serves as a practical ethical principle that governs human thoughts, words, and behaviour in addition to being a religious ideal. The study also explores other major Jain ethical principles such as satya (truthfulness), asteya (non-stealing), brahmacharya (self-restraint), and aparigraha (non-possession), which collectively reinforce the moral discipline required for ethical living and spiritual advancement. The study also covers the philosophical theory of anekāntavāda, which promotes tolerance and communication in pluralistic society by encouraging intellectual humility and respect for different points of view. The study makes the case that Jain ethics offers important insights for fostering peace, sustainability, and societal harmony by placing these ethical principles inside modern contexts like violence, consumerism, environmental degradation, and ideological struggle. In the end, the study shows that Ahimsa as a way of life has lasting philosophical significance and can greatly aid in the creation of a more sympathetic and morally upright world community.